Digital Literacy for Christian Educators: Integration of Technology Competencies and Theological Values in Christian Education Learning - Kristiani Yanti Kana (Indonesian Journal of Christian Education and Theology, 2026)
This study aims to analyze the importance of digital literacy for Christian educators in integrating technological competencies with theological values in Christian Religious Education (CRE) learning. The rapid development of digital technology requires educators not only to master technical skills but also to utilize technology ethically, reflectively, and contextually in accordance with Christian faith principles. The research employs a qualitative approach using literature review and conceptual analysis of various theoretical sources and educational practices. The findings indicate that digital literacy for Christian educators encompasses pedagogical, critical, and spiritual competencies in using technology as a meaningful learning tool. The integration of theological values in technology use contributes to shaping students who are not only digitally competent but also possess strong moral and spiritual integrity.